2006
DOI: 10.1111/j.1540-8167.2006.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Electrophysiological Effects of Components of Acute Ischemia in Langendorff‐Perfused Rat Hearts Using Voltage‐Sensitive Dye Mapping

Abstract: These results provide the necessary background information for interpreting electrophysiological measurements during acute ischemia in the presence of cytochalasin-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Several studies using optical mapping have demonstrated that APD is shortened during low flow ischemia. [27][28][29] However, in the current study, we induced global ischemia. Under these experimental conditions, our high resolution imaging device detected only weak change in fluorescence, therefore, we could not record the APD during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using optical mapping have demonstrated that APD is shortened during low flow ischemia. [27][28][29] However, in the current study, we induced global ischemia. Under these experimental conditions, our high resolution imaging device detected only weak change in fluorescence, therefore, we could not record the APD during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may simply reflect the increased variability in the response in both types of hearts as the effect approaches conduction failure. Finally, we (36) have previously determined that moderate activation of I K,ATP does not significantly affect CV in control hearts. The effects of I K,ATP on conduction were therefore not considered further in this work.…”
Section: Conduction Slowing During Acute Ischemia In Stz-induced Diabmentioning
confidence: 97%
“…Blebbistatin’s toxicity and side effects on ion channels are less pronounced compared to other electromechanical uncouplers, such as cytochalasin D [29] and 2,3-butanedione monoxime [14, 22, 24]. Its main known limitations include photosensitivity and phototoxicity [19, 30].…”
Section: Introductionmentioning
confidence: 99%